Multi-Document Summarization using CS-ABC Optimization Algorithm - Chandra Kumar, K.; Nagalla, Sudhakar (EAI Endorsed Transactions on Energy Web, 2020)
In revolve handle to the information excess, the dramatic boost up documents, on the WWW, show the way of the accessibility of various credentials through the equal subject with conception. Within a limited time, a hard to inquire a suitable a particular document associated to a specific topic to fulfils user’s compound data conditions. Hence, we have followed an effective document summarization system applying SVM classifier strategy by this paper. For choosing optimal sentence sets, the proposed technique applies the hybrid ABC-CS optimization algorithm. Further, established on few relevant features, SVM classifier approach is applied in finding the summary by ranking each of the optimal sentences. The operational proposal of JAVA and the results were examined for the methodology is implemented.